Gas Oil Components And The Effects Of The Changing Gas Oil Quality Requirement - A.S. Nasution; E. Jasjfi (Testing Center for Oil and Gas LEMIGAS, 1998)
The survey of gas oil production and impact of more stringent specification on the catalyst performance of ASEAN refineries conducted in 1996 revealed that a total feedstock of 5,673 MBPSD are processed into 1,131 MBPSD gas oil. This consist of the following product distribution: straight-run gas oil 85.44%, thermal cracked gas oil 2.52% cat. Cracked gas oil 3.50% and hydrocracked gas oil 8.54% on total gas oil products. About 50% of this total gas oil is processed in hydrotreating processes to improve the performanceof diesel oil.This paper reviews the production of gas oil components in ASEAN and the effect of the changing gas oil quality requirement on hydrotreating catalyst performance.